2019
DOI: 10.1088/1755-1315/348/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on growth, survival and feed efficiency in three generations of domesticated Asian redtail catfish Hemibagrus nemurus (Valenciennes, 1840)

Abstract: Domestication is one of the important steps in culturing wild fish into a captive system. This study aimed to evaluate the growth, survival rate, and feed efficiency of three generations (G-1, G-2, and G-3) of domesticated Asian redtail catfish. This study was conducted in the wet laboratory of Research Institute for Freshwater Aquaculture and Fisheries Extension (RIFAFE) Bogor from October to December 2017. The Completely Randomized Experimental Design with three treatments and three replications were utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…Likewise, the coefficient variance value was higher in the bodyweight than that of the length of the fry of javaean barb in the first generation. This fry growth rate pattern was similar to the growth pattern of asian redtail catfish [12]. This indicates that the influence of the environment was more significant on weight gain than the length.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Likewise, the coefficient variance value was higher in the bodyweight than that of the length of the fry of javaean barb in the first generation. This fry growth rate pattern was similar to the growth pattern of asian redtail catfish [12]. This indicates that the influence of the environment was more significant on weight gain than the length.…”
Section: Resultssupporting
confidence: 72%
“…This indicates that the influence of the environment was more significant on weight gain than the length. The feed conversion ratio of javaean barb in the frying phase was relatively higher than that of Asian redtail catfish, which was 1.58 ± 0.02 [12]. A feed conversion ratio is an indicator to measure the effectiveness of the feeding and the quality of feed [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cohort peaks in the recruitment pattern of Hemibagrus nemurus showed that the spawning time is done in the same periods, from June to July each year. This pattern is adequate related to the migration properties of this species, that they will close to the floodplain for spawning in the dry season and wait for the rainy season [18]. The spawning of blackfish and some freshwater fish has a relation with fluctuation of the rainy season and water level [19].…”
Section: Recruitment Patternmentioning
confidence: 93%
“…baung (Hemibagrus nemurus) merupakan komoditas ikan yang bernilai ekonomi tinggi yang berasal dari air tawar dan sangat populer di kalangan masyarakat dalam negeri maupun wilayah Asia Tenggara (Kurnia et al, 2022) serta menjadi salah satu komoditas potensial bagi keragaman usaha budidaya perikanan di Indonesia (Lusiastuti, 2019;Radona et al, 2019). Namun, ikan ini belum dapat dibudidayakan secara intensif karena rendahnya produksi benih ikan tersebut (Cahyanurani et al, 2023), dimana rendahnya tingkat kelulushidupan dan lambatnya pertumbuhan benih ikan baung (Lusiastuti, 2019;Sinaga et al, 2021).…”
Section: Ikanunclassified